The Influence of Professional Competence and Affective Commitment on Job Satisfaction: Study at The Government Agencies in West Bandung Regency - Imam Heryanto; Kadir Kadir (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
This research was conducted to determine the effect of professional competence and affective commitment on employee job satisfaction. This research was conducted at one of the official offices in West Bandung Regency, where the method used was descriptive and verification methods, with 71 respondents. The data analysis technique used was the path analysis technique to determine the effect of both direct and indirect independent variables. Based on the results of the study shows that professional competence is in the relatively good category. Affective commitment is in the good enough category. Moreover, employee job satisfaction is in the reasonably good category. Based on statistical data processing, it appears that the total professional competence variable has an effect of 24.7%. The total effect of the affective commitment variable is 40.1%. The variables of professional competence and affective commitment to job satisfaction were 64.8%. Meanwhile, other factors that were not studied and contributed to job satisfaction shown by the value of Pyε = 0, 35.2, or 35.2%. Professional competence and affective commitment affect job satisfaction. This result shows that the higher the professional competence of employees and the increase in employee affective commitment, the higher the employee job satisfaction. Other variables affect employee satisfaction, such as motivation, compensation, organizational culture, and other factors not included in this study.